(untitled) (Research, Society and Development, 2020)
Teaching strategies as active methodologies in education are of great importance in the educational field, as they contribute to the integration of students in the teaching and learning process. Based on this premise, this article aims to address two active methodologies as a teaching strategy adopted in the process of training teachers in the Pedagogy course in Integrated Pedagogical Action II - Supervised Internship at the Tangará da Serra Faculty of Education and, therefore, the application with Elementary School students of a municipal public school. The strategies chosen and applied in the fifth semester of Pedagogy refer to the GV-GO (Verbalization Group and Observation Group) and PBL (Problem-Based Learning). As a result, through the students’ observations and reports, the active methodologies were well accepted, having unanimous approval as teaching strategies, both by the academics who developed them and by the students in the pedagogical intervention room. The use of differentiated methodology enabled greater involvement and participation of students, implying a more dynamic and meaningful learning in the learning process of both classes.